Legality and legitimacy - Schmitt, Carl, 1888-1985 (Duke backfile, 2004)
Carl Schmitt ranks among the most original and controversial political thinkers of the twentieth century. His incisive criticisms of Enlightenment political thought and liberal political practice remain as shocking and significant today as when they first appeared in Weimar Germany. Unavailable in English until now, Legality and Legitimacy was composed in 1932, in the midst of the crisis that would lead to the collapse of the Weimar Republic and only a matter of months before Schmitt's collaboration with the Nazis. In this important work, Schmitt questions the political viability o.